Practical Implementation of an Android-based Application for Mail Archiving at the Civil Registry Office of Bangka Regency - Irawan, Devi; Fitriyani, Firiyani; Wahyuningsih, Delpiah; Yanuarti, Elly; Yuranda, Rezky (JATISI, 2025)
Letter archives are an important aspect for every office or organization, such as at the Civil Registry Office of Bangka Regency. The letter archiving system at the Civil Registry Office of Bangka Regency is still managed manually. Therefore, several problems often occur, including time-consuming archive searches, data duplication, and the potential loss of important documents. To address these issues, a more flexible and dynamic archiving system is needed so that tasks can be carried out more quickly and efficiently. Through digital archiving, not only does it improve the quality of government administration, but it also demonstrates a commitment to providing public services that are more modern, transparent, and responsive. The method used in implementing this application is the prototype method, and the tool used is Android Studio. This application can serve as a solution for employees to record, store, and access letter data digitally via Android devices without relying on manual records. This accelerates the archive search process, reduces the risk of data loss, and increases the accuracy of document management.